2003
DOI: 10.1111/j.0014-3820.2003.tb01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Isolation and Phylogenetic Divergence in Neurospora: Comparing Methods of Species Recognition in a Model Eukaryote

Abstract: We critically examined methods for recognizing species in the model filamentous fungal genus Neurospora by comparing traditional biological species recognition (BSR) with more comprehensive applications of both BSR and phylogenetic species recognition (PSR). Comprehensive BSR was applied to a set of 73 individuals by performing extensive crossing experiments and delineating biological species based on patterns of reproductive success. Within what were originally considered two species, N. crassa and N. interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
238
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(250 citation statements)
references
References 66 publications
5
238
2
Order By: Relevance
“…This reinforcement is very important because speciation involves not only divergence, but also maintenance, mainly when the derived species coexist [81]. Dettman et al [87] showed how these barriers to inter-species interbreeding may be different between allopatric and sympatric species of Neurospora; they observed a higher reproductive success for allopatric heterospecific pairings than for sympatric ones.…”
Section: Emergence Of New Variants Of the Pathogenmentioning
confidence: 99%
“…This reinforcement is very important because speciation involves not only divergence, but also maintenance, mainly when the derived species coexist [81]. Dettman et al [87] showed how these barriers to inter-species interbreeding may be different between allopatric and sympatric species of Neurospora; they observed a higher reproductive success for allopatric heterospecific pairings than for sympatric ones.…”
Section: Emergence Of New Variants Of the Pathogenmentioning
confidence: 99%
“…generally differ in sterility in a small, and occasionally in a high degree,'' citing Kölreuter and Gärtner, the same plant hybridizers whose hundreds of intra-and interspecific crosses inspired Mendel in 1865 (translated in Bateson 1901). Asymmetry was subsequently found in essentially all systems subject to systematic hybridization experiments, including many invertebrates (e.g., Muller 1942;Oliver 1978;Harrison 1983;Coyne and Orr 1989a;Gallant and Fairbairn 1997;Presgraves and Orr 1998;Navajas et al 2000;Willett and Burton 2001;Presgraves 2002), vertebrates (e.g., Thornton 1955;Rakocinski 1984;Bolnick and Near 2005), and fungi (e.g., Dettman et al 2003). A recent analysis of reciprocal species crosses within 14 diverse angiosperm genera found significant isolation asymmetry in 35-45% of all species pairings, evaluated at three different postmating stages of reproductive isolation (Tiffin et al 2001).…”
mentioning
confidence: 99%
“…The partition homogeneity test of the combined regions conducted in PAUP resulted in a P-value of 0.01, thus lower than the conventionally accepted value of 0.05 required to combine data. However, several studies have accepted P-values greater than 0.001 (Cunningham 1997;Dettman et al 2003) and a decision was made to do so in this case. The parsimony analysis of the combined dataset resulted in the retention of 91 most parsimonious trees (TL = 316, CI = 0.854, RI = 0.968, RC = 0.827, HI = 0.146).…”
Section: Identification Of Isolatesmentioning
confidence: 99%